Augmentation of bone formation by sympathectomy in rats as evaluated by [99mTc]Tc-MDP - Cai, Zili; Lin, Xiuting; Zhuang, Yuehong; Miao, Weibing; Xie, Yun (Frontiers in Endocrinology, 2025)
BackgroundThe role of the sympathetic nervous system in bone metabolism remains unclear. Given that 99mTc-methylene diphosphonate ([99mTc]Tc-MDP) uptake reflects active bone formation and mineralization, this study aims to investigate the effects of sympathetic denervation on bone formation in rats using [99mTc]Tc-MDP SPECT/CT imaging.Materials and methodsTwenty rats were randomly assigned to a superior cervical ganglionectomy (SCGx) group (n = 10) or a sham-operated control group (n = 10). Circular cranial fractures were surgically created in both groups. Micro SPECT/CT imaging was performed at 3, 6, and 9 weeks postoperatively to assess bone mineral density (BMD), bone volume/tissue volume (BV/TV), and bone volume (BV). In a separate experiment, 12 additional rats underwent either bilateral lumbar sympathectomy (n = 6) or sham operation (n = 6). At 9 weeks, [99mTc]Tc-MDP biodistribution in harvested bone tissues was measured. Immunohistochemical staining for tyrosine hydroxylase (TH) and Ki67 was used to evaluate sympathetic innervation and cell proliferation in craniums, while immunofluorescence co-labeling for Ki67 and osteopontin (OPN) identified proliferating osteoblasts. In vitro, MC3T3-E1 osteoblasts were treated with norepinephrine (NE) or control medium for 24 hours. Cell proliferation was assessed using EdU staining. Additionally, sympathetic neurons isolated from neonatal rats were co-cultured with MC3T3-E1 cells in Transwell systems, and mineralization and alkaline phosphatase (ALP) activity were evaluated.ResultsSuccessful SCGx was confirmed by signs of Horner’s syndrome. SCGx rats exhibited significantly higher [99mTc]Tc-MDP uptake and increased BMD, BV/TV, and BV in peri-fracture regions at all time points (p < 0.0001). Lumbar sympathectomy increased tracer uptake in femurs, tibias, lumbar vertebrae, and sacra (p < 0.01), but not in cervical or thoracic vertebrae. TH expression decreased, while Ki67 and OPN levels increased in SCGx craniums. NE suppressed MC3T3-E1 proliferation (p < 0.0001), and co-culture with sympathetic neurons reduced mineralization and ALP activity (both p < 0.0001).ConclusionSympathectomy can enhance osteoblast prolifeation and augment bone formation, which can be effectively assessed and quantified using [99mTc]Tc-MDP SPECT/CT imaging.